Ministry of Trade and Industry Decree No. 30 of the Year 2018 on Amending the Table attached to the Executive Regulations of the Law on Facilitating the Procedures of Licensing the Industrial Establishments = وزارة التجارة والصناعة قرار رقم 30 لسنة 2018 بشأن تعديل الجدول المرفق باللائحة التنفيذية لقانون تيسيرت إجراءات منح تراخيص المنشآت الصناعية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic